3D Ln-MOFs as multi-responsive luminescent probes for efficient sensing of Fe3+, Cr2O72−, and antibiotics in aqueous solution. Issue 21 (11th May 2021) - Xue, Yun-Shan; Ding, Ji; Sun, Dan-Ling; Cheng, Wei-Wei; Chen, Xuan-Rong; Huang, Xing-Cai; Wang, Jun
Abstract : Two families of Ln-based MOFs with 3D structures have been synthesized under solvothermal conditions. Eu-MOF (4 ) can act as a multi-responsive luminescent probe in water systems and Dy-MOF (6 ) shows slow magnetic relaxation behaviors. Abstract : Two families of lanthanide metal–organic frameworks (Ln-MOFs), namely [Ln2 L2 (DMF)4 ]· x DMF· y H2 O n (Ln = Ce(1 ), Pr(2 ), Sm(3 ), Eu(4 ), Gd(5 ); x = 0, 1; y = 0, 1) and [Ln2 L2 (H2 O)2.5 ] n (Ln = Dy(6 ), Ho(7 )), have been solvothermally synthesized based on the semi-rigid tripodal ligand 5-(4-carboxybenzyloxy)isophthalic acid (H3 L). Utilizing the excellent luminescence property and water stability, Eu(4 ) exhibited efficient luminescence responses toward Fe 3+, Cr2 O7 2−, and NFT/NZF antibiotics in aqueous medium with high sensitivity and selectivity. The detection limits (LODs) are 3.69 μM for Fe 3+ ion, 4.01 μM for Cr2 O7 2− anion and 9.92 μM/11.4 μM for NFT/NZF antibiotics, suggesting that Eu(4 ) is a good and simple multifunctional luminescent sensor. Additionally, the Gd(iii ) ions exhibit a weak antiferromagnetic interaction in the dinuclear SBUs of Gd(5 ), and Dy(6 ) shows slow magnetic relaxation behaviors under zero dc field.